Do firms react to monetary policy in developing countries? - Djeneba Dramé; Florian Léon (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
The debate on the effectiveness of monetary policy in developing countries remains open. We shed new light on this issue by examining whether managers' perceptions of financial constraints are shaped after a change in monetary policy. Our analysis shows that managers are more likely to report increased financial constraints following an increase in the policy rate, only if the change is sufficiently important (more than 100 basis points). Interestingly, this adjustment appears to be symmetric, occurring for both easing and tightening. Moreover, our results suggest that the most sensitive firms are those with a prior credit relationship and those operating in countries with a competitive financial system and an independent central bank. Finally, we show that monetary policy affects not only perceptions but also firms' decisions to apply for credit.
Keywords: 330; Monetary policy